Inducible nitric oxide synthase and guinea-pig ileitis induced by adjuvant - N. D. Seago; J. H. Thompson; X.-J. Zhang; S. Eloby-Childress; H. Sadowska-Krowicka; J. L. Rossi; M. G. Currie; P. T. Manning; D. A. Clark; M. J. S. Miller (Hindawi Limited, 1995)
We sought to establish a model of inflammatory bowel disease by augmenting the activity of the local immune system with Freund's complete adjuvant, and to determine if inducible nitric oxide synthase (iNOS) expression and peroxynitrite formation accompanied the inflammatory condition. In anaesthetized guinea-pigs, a loop of distal ileum received intraluminal 50% ethanol followed by Freund's complete adjuvant. Control animals were sham operated. When the animals were killed 7 or 14 days later, loop lavage fluid was examined for nitrite and PGE2 levels; mucosal levels of granulocyte and macrophages were estimated by myeloperoxidase (MPO) and N-acetyl-D-glucosaminidase (NAG) activity, respectively. Cellular localization if iNOS and peroxynitrite formation were determined by immunohistochemistry with polyclonal antibodies directed against peptide epitopes of mouse iNOS and nitrotyrosine, respectfully. Adjuvant administration resulted in a persistent ileitis, featuring gut thickening, crypt hyperplasia, villus tip swelling and disruption, and cellular infiltration. Lavage levels of PGE2 and nitrite were markedly elevated by adjuvant treatment. Immunoreactive iNOS and nitrotyrosine bordered on detectability in normal animals but were markedly evident with adjuvant treatment at day 7 and particularly day 14. Immunohistochemistry suggested that enteric neurons and epithelia were major sites of iNOS activity and peroxynitrite formation. We conclude that local administration of adjuvant establishes a chronic ileitis. Inducible nitric oxide synthase may contribute to the inflammatory process.